Dodicesima Conferenza Nazionale ASITA - Redazione, Redazione (GEOmedia, 2008)
12th ASITA national conference The article features a report from the 12th ASITA national conference which was held in L'Aquila last october. The conference is the main event on the Italian calendar in which the academic and commercial issues regarding Earth sciences meet.